Of boredom and havoc: Correctional officers and meaning making - Spencer, Dale (Punishment & society, 2025)
Despite early calls to pay attention to the role of emotions in crime and criminal justice, including in prison studies, empirical research focusing on emotions in the administration of criminal justice has been sporadic. With notable exceptions, little attention has been paid to the role of boredom, meaning, and the labour processes of criminal justice personnel more broadly, and correctional officers specifically. We fill the lacuna in knowledge by examining the relationship between boredom, temporality, the labour process of correctional officers, meaning making, and officer wellness. We first offer an overview of boredom as an emotion and its contribution to meaning making. We then outline the labour process of correctional officers, reviewing literature on the structure of their carceral work environments and their experiences of boredom. We draw on 651 interviews with correctional officer recruits (n = 375) and follow-up interviews with correctional officers (n = 276) within federal prisons across Canada to understand the emotional experiences of correctional work, specifically focusing on boredom as a dominant emotion and its effect on officer wellness. Our study uses a phenomenological approach to consider how boredom plays a role in the daily lives of those providing security within prison spaces, how prison officers make sense of their work in relation to temporality and boredom, and how boredom and havoc contributes to poor officer wellness.